Immunohistochemical Expression of Extracellular Matrix Protein-1 in Neoplastic Thyroid Lesions - Khan, Nazoora; Ansari, Hena Ayyub; Hasan, Naba; Khan, Mohammad Amanullah (Annals of Pathology and Laboratory Medicine, 2020)
Background: Upregulated Extracellular matrix protein 1 (ECM 1) expression has been observed in several malignancies including breast, thyroid carcinoma, cutaneous melanoma and gastric carcinoma. ECM 1 expression has been evaluated in various epithelial malignancies using real time – reverse transcriptase polymerase chain reaction (RT-PCR). The purpose of current study is to evaluate the immunohistochemical expression of ECM 1 in various neoplastic lesions of thyroid. Methods: The study included 81 neoplastic thyroid tissue specimens (21 benign and 60 malignant lesions) received over a period of 5 years (2012-2017). Hematoxylin and Eosin stained sections of the tissue specimens were carefully examined under light microscope in order to establish the histopathological diagnosis. The immunohistochemical marker ECM 1 was applied on appropriate sections and the slides were evaluated accordingly. Result: The expression of ECM 1 was nil (grade 0, 47.62% cases) or weak (1+, 52.38% cases) in benign lesions while majority of malignant lesions (78.33%) showed strong homogenous and crisp staining (3+). The difference in the expression of ECM 1 between benign and malignant lesions was found to be statistically significant (p < 0.001). ECM 1 has a diagnostic accuracy of 0.82 and sensitivity of 100% in differentiating benign from malignant lesions. Conclusion: ECM 1 is uniformly upregulated in all malignant thyroid neoplasms irrespective of the histological type of malignancy. Immunohistochemical expression of ECM 1 shows comparable results to RT-PCR. ECM 1 immunohistochemistry can thus serve as an important standalone marker of malignant thyroid tissue.